Ada Apa di Balik Belum Berhasinya Reforma Agraria di Indonesia? - Nevia Cahyana , Intan (Universitas Ekasakti, 2024)
This article aims to find out what are the problems and obstacles that are not well-implemented agrarian reform in Indonesia, and what recommendations that can be implemented so that agrarian reform runs properly. This research is a normative type of research conducted by examining library materials, also known as literature studies. Agrarian reform in Indonesia is faced with several problems that include inequality of land ownership, uncertainty of land ownership status, as well as conflict over land rights, and uncertainty of land ownership status and lack of law enforcement exacerbate the situation, causing uncertainty and conflict to the detriment of rural communities. Industrial expansion and development projects also place significant pressure on land resources and community land rights. The growth of the plantation, mining, and infrastructure sectors often has negative impacts on rural communities and the environment, complicating agrarian reform efforts. Resolving these issues requires a strong commitment from the government, collaboration between various parties, and progressive policy implementation to achieve inclusive and sustainable agrarian reform.